Queer phantom critters - Penney, James (Filozofski vestnik, 2025)
What are the contemporary forms of the Foucauldian historicism that Read My Desire sought to correct? In the theoretical humanities, the most insurgent variant is surely the revival of the turn not to the real, but to reality; to the material or phenomenal and, ulti-mately, to being as such. Generally speaking, this contemporary orientation of thought aims either to emancipate humanity from the determinative distortions of subjectivity, of the transcendental constitution of apperception, or else dislodge this human func-tion from the privilege of its presumed centrality, thereby relegating it to the same plane occupied by every other animate and inanimate being. As this paper argues, the agen-tial realist’s definition of causality, despite its claims to complexity and indetermina-cy (not to mention a lineage that connects back to the same structuralist linguistics that shaped Lacan’s thought), is ultimately guilty on the charge of historicism. Precisely in their allergy to the strange causal faculty of negativity, the argument’s conceptions of “material-discursive interactions” and “intra-agential spactimematterings” are the crime’s telltale clues. In short, the ambiguously defined relation of discourse to a con-sistently indeterminate idea of matter, and the subsequent disappearance of discourse’s non-closure or incompletion from the causal field, not only obfuscates the signifier’s retroactive creationist powers, but also renders illegible what we might call the desire of the empirical natural sciences in both their humanist-progressivist and properly un-conscious forms.
Keywords: causality; homoseksualnost; Lacan, Jacques; microbiology; mikrobiologija; psihoanaliza; psychoanalysis; realism; realizem; science; vzročnost; znanost